Optical biosensor for on-line monitoring of organophosphate pesticides in water (2023)
ABSTRACT : Water sources in rural areas are exposed to Chlorpyrifos (CPF) and other harmful organophosphate pesticides (OPs) that should be detected before human consumption, and biosensors have emerged as promising alternatives. The application of nanomaterials, including carbon quantum dots (CD), can significantly improve the performance of optical biosensors. In this work, naturally fluorescent and non-toxic CD were synthesized from African oil palm biochar, in cooperation with the GIBEC research group from Universidad EIA. The CD were integrated and evaluated with two biomolecules and the systems were modulated with Graphene Oxide (GO) producing two fluorescent probes. The first system was developed based on Acetylcholinesterase enzyme (AChE); this biosensor was assessed under pure chlorpyrifos (CPF), but also under a commercial formulation called Lorsban® obtaining a limit of detection (LOD) as low as 0.13 µg L-1 and 2.05 µg L-1 for CPF and Lorsban® respectively. The second system employed a DNA aptamer to detect CPF and, showed a LOD as low as 0.01 µg L-1 with great selectivity. To advance in the field application of fluorescent probes, a portable device was designed, constructed, and evaluated in cooperation with the GIMEL research group from Universidad de Antioquia. Finally, the AChE system was selected for the evaluation of 9 superficial water samples from different rural locations of Antioquia, Colombia, using the portable prototype. The results showed that some physicochemical parameters of natural water sources have an influence on the performance of the system. However, the prototype could detect CPF in real samples from 1 µg L-1 and using only 150 µL of the sample. The advantages of the developed nanostructured fluorescent probes using along with a portable device tailored-made for the application, open the way for future commercial applications. To the best of our knowledge, this is one of the few works reporting the integration of nanomaterials with different biomolecules in optical systems for the detection of pesticide formulations in real prototypes, with promising results.